Educational activity of a community nurse when performing the prevention of diabetes complications in a primary health care centre - Zajančkauskienė, Zita; Šinkūnienė, Ramūnė (Slauga. Mokslas ir praktika, 2020)
Diabetes is one of the most spread metabolic disorders all around the world. By the data of the World Health Organization (WHO) diabetes makes 5 percent of all the deaths in the world [1]. Diabetes is not curable, however, this disease can be controlled and managed, and it is essential to increase the accessibility to selfmonitoring education. Educational activity of a community nurse is targeted at the training of selfmonitoring of diabetes. When performing the prevention of diabetes, a community nurse informs society about the causes and effect of diabetes, consults patients and helps understand the scope of diabetes, encourages the early diagnostics of diabetes, and promotes healthy way of living. The aim of the research is to analyse the educational activity of a community nurse when performing the prevention of diabetes complications in a primary health care centre.The objectives of the research are as follows: to investigate the knowledge of the patients ill with diabetes about the causes, complications and selfmanagement of diabetes; to assess the attitude of the people ill with diabetes towards the organization of education; to investigate the educational needs of the people ill with diabetes; to carry out the analysis of an educational activity of a nurse.The methods of the research: There was a qualitative research carried out October – December 2015 in a family medicine clinics of a primary health care centre in a district X. The method of inquiry was a semistructured interview. The research involved 6 community nurses and 6 patients ill with diabetes. The respondents have been selected by targeted selection. The research outcomes allowed formulating the following main conclusions: after having analysed the knowledge of the patients ill with diabetes it has come to light that they are sufficiently informed about the causes and consequences of the disease, therefore, they perform regular selfmonitoring – they measure the sugar level in their blood. They know that this is essential for the people ill with diabetes, because the maintenance of appropriate level of glucose in blood helps avoiding the consequences of a shorttime health disorder and longterm complications. The attitude of the patients towards initial education is totally positive. The education process of the patients ill with diabetes starts straight after the disease is diagnosed. In order to manage a disease a patient faces the need to learn selfmonitoring and a nurse needs to teach it. The educational activity of a community nurse performed in the primary health care centre is significant for it continuously updates the patients’ knowledge on the disease, provides with new knowledge, the patients are encouraged and trained to monitor the disease.
Keywords: diabetes; educational activity; a nurse